Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1755-8794-6-53
|View full text |Cite
|
Sign up to set email alerts
|

Integrated molecular portrait of non-small cell lung cancers

Abstract: BackgroundNon-small cell lung cancer (NSCLC), a leading cause of cancer deaths, represents a heterogeneous group of neoplasms, mostly comprising squamous cell carcinoma (SCC), adenocarcinoma (AC) and large-cell carcinoma (LCC). The objectives of this study were to utilize integrated genomic data including copy-number alteration, mRNA, microRNA expression and candidate-gene full sequencing data to characterize the molecular distinctions between AC and SCC.MethodsComparative genomic hybridization followed by mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 37 publications
(38 reference statements)
2
49
0
Order By: Relevance
“…Using gene expression profiling techniques, prior studies also demonstrated that adenocarcinoma and squamous cell NSCLCs have different expression portfolios (2,14), which is in line with our observation that the association between TP53 mutations and increased VEGF-A transcripts appears specific for adenocarcinoma of the lung. It is conceivable that the improved outcome that was previously reported by our group (5) in bevacizumab-treated patients who harbored TP53 mutations versus wild-type TP53 is due to the association between TP53 mutations and higher VEGF-A, the target for bevacizumab.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Using gene expression profiling techniques, prior studies also demonstrated that adenocarcinoma and squamous cell NSCLCs have different expression portfolios (2,14), which is in line with our observation that the association between TP53 mutations and increased VEGF-A transcripts appears specific for adenocarcinoma of the lung. It is conceivable that the improved outcome that was previously reported by our group (5) in bevacizumab-treated patients who harbored TP53 mutations versus wild-type TP53 is due to the association between TP53 mutations and higher VEGF-A, the target for bevacizumab.…”
Section: Resultssupporting
confidence: 77%
“…A diagnosis of NSCLC carries a grim prognosis; 5-year survival is less than 15% (2). Bevacizumab is an antibody that targets vascular endothelial growth factor-A (VEGF-A).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the biomarker testing was limited to NGS. Integration of transcriptomic and/or proteomic biomarkers may provide additional information in future studies (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is the primary histological classification of lung cancer [2]. There are three histologic subtypes of NSCLC: squamous cell carcinoma (SCC), adenocarcinoma (AC), and large-cell carcinoma (LCC) [3]. Overall, 5-year survival of NSCLC has remained at 15 % for the last two decades and the prognosis of patients with NSCLC principally correlates with tumor invasion and metastasis [4].…”
Section: Introductionmentioning
confidence: 99%